First, set up an equation that models this statement.
N is your variable because it’s the unknown Number.
8n-13=43
Then, add 13 on both sides so you have the variable and it’s coefficient alone.
8n-13=43
+13.+13
________
8n=56
Then, divide the variable and the coefficient by the coefficient.
8n=56
—. —
8. 8
Now you have your variable all by itself, and you have the persons number.
n=7
Your number is 7.
Answer:
-1
Step-by-step explanation:
-2(x-7)=16
-2x +14=16 You distribute
-14 -14
-2x = 2
-2 -2 you divide
and get -1 as your answer.
Hope my answer has helped you!
Answer:
-3k + 10
Step-by-step explanation:
-3k - (-8) + 2
-3k + 8 + 2 !!
-3k + 10 → simplified version of the given expression
!! → We got rid of the parenthesis by combining the two negative signs. The rules state that any 2 identical signs combined (in this case, - and -) equal a positive sign (+).
Hope it helped,
BiologiaMagister
Since this is a triangle all the angles within the triangle add up to 180 degrees so....
82+(9x+2)+(7x)=180
82+2+16x=180
16x+84=180
16x=96
X=6
If we plug in X to angle(9x+2) and angle (7x) we will get 56 and 42. We can get angle 2 by subtracting 180-42 which is 138
FINAL ANSWER: 138 degrees
X=2 because first you have to combine like terms. Than you have to bring the Varible on one side. Finally you solve for the Varible and you get the answer2.